Activation of the polycomb repressive complex pathway in the bone marrow resident cells of diffuse large B-cell lymphoma patients. Issue 8 (2nd August 2016) - Oh, Eun Ji; Kim, Eun Kyung; Yang, Woo Ick; Yoon, Sun Och
Abstract: The present study investigated the activation of polycomb repressive complex 2 (PRC2) pathway proteins in the resident cells within the bone marrow hematopoietic microenvironment of diffuse large B-cell lymphoma (DLBCL) patients. PRC2 proteins (enhancer of zeste homolog 2, suppressor of zeste 12 homolog, and embryonic ectoderm development), histone methylation mark (H3K27me3), and c-MYC activation were evaluated in pretreatment bone marrow from 208 DLBLC patients. Positive expression of the PRC2, H3K27me3, and c-MYC in the bone marrow resident cells was more frequent in cases with bone marrow involvement of tumor. The expression among PRC2, H3K27me3 mark, and c-MYC was closely correlated. Positive PRC2 expression in bone marrow resident cells was significantly associated with inferior progression-free survival (PFS) and overall survival (OS) and determined to be an independent prognostic factor of inferior PFS and OS. In conclusion, the PRC pathway was frequently activated in bone marrow resident cells of DLBCL patients, and PRC activation was tumor-related and associated with poor clinical outcomes.